Possibilities of improving the learning quality of mathematics in Kaunas University of Technology - Novikienė, Regina; Matiukaitė, Rasa (Lietuvos matematikos rinkinys, 2009)
The learning quality of mathematics is perceived in the article from educational perspective as the existence of arranged educational system that allows implementing the aims of the course taught. The article reveals the possibilities of improving the quality while teaching first year students of Kaunas University of Technology. The conclusions are based on student test results, the analysis of scientific literature and practical experience of the authors.
Keywords: possibilities; learning quality